2002
DOI: 10.1038/sj.mp.4001158
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of synapsin in the hippocampus of patients with bipolar disorder and schizophrenia

Abstract: Several studies suggest that decreased expression of presynaptic proteins may be characteristic of schizophrenia. We examined one such protein, synapsin, in schizophrenia and bipolar disorder. Samples of hippocampal tissue from controls (n = 13), patients with schizophrenia (n = 16), or bipolar disorder (n = 6), and suicide victims (n = 7) were used. The membrane and cytosolic fractions were analyzed by Western immunoblotting for synapsin using an antibody that detects synapsin Ia, IIa, and IIIa proteins. Syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
103
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(110 citation statements)
references
References 39 publications
5
103
0
1
Order By: Relevance
“…In rat cortex, previous studies have shown that synaptophysin and PSD-95 levels do not exhibit significant decreases with PMI less than 72 hours (Halim et al 2003;Hilbig et al 2004;Siew et al 2004). In human cortex, synaptophysin levels appear to be fairly robust over PMIs of less than 84 hours (but see Vawter et al 2002) (Honer et al 1992Vawter et al 2002). These findings are consistent with our study of the postmortem stability of synaptophysin in rat cortex over 24 hours.…”
Section: Discussionsupporting
confidence: 82%
“…In rat cortex, previous studies have shown that synaptophysin and PSD-95 levels do not exhibit significant decreases with PMI less than 72 hours (Halim et al 2003;Hilbig et al 2004;Siew et al 2004). In human cortex, synaptophysin levels appear to be fairly robust over PMIs of less than 84 hours (but see Vawter et al 2002) (Honer et al 1992Vawter et al 2002). These findings are consistent with our study of the postmortem stability of synaptophysin in rat cortex over 24 hours.…”
Section: Discussionsupporting
confidence: 82%
“…35 A recent study showed both total and individual synapsins to be reduced in the hippocampus of patients with schizophrenia and bipolar disorder, as well as victims of suicide 36 while SYN2 was here observed to be elevated in depressed suicides (area 45). Lastly, multiple probe sets for QKI identified a common pattern of downregulated expression in depressed suicides across all four brain regions studied.…”
Section: Discussionmentioning
confidence: 45%
“…Release of glutamate from nerve endings was markedly decreased in the synapsin I mutant mice (Li et al, 1995). The total synapsin (Ia, IIa, and IIIa) protein was reduced in the hippocampus of patients with bipolar disorder, another type of depression besides major depression, implying that altered or reduced synaptic function in the hippocampus may be involved in this disorder (Vawter et al, 2002). In our study, we found that the density of synapsin I immunoreactive synaptic buttons increased significantly in the CA3 subfield after 21 days CUMS.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic treatment with tranylcypromine, but not desipramine or fluoxetine, decreases synapsin I mRNA expression in rat hippocampal DG, CA3, and CA1 (Rapp et al, 2004), and imipramine or fluvoxamine decreases synapsin I immunoreactivity in rat hippocampus (Iwata et al, 2006). Another study showed that injecting rats with lithium for 30 days produces no changes in total synapsin in the hippocampus (Vawter et al, 2002). The effects of mifepristone on the mRNA level of synapsin I are not quite the same as tranylcypromine.…”
Section: Discussionmentioning
confidence: 98%